As marcas do autor em O Ano da Morte de Ricardo Reis, de José Saramago - Santana, Jaderson Soares (2016)
This research is devoted to study the authorial traits in the fictional prose of José Saramago. His novels, despite imaginative, are impregnated with intrusions and comments. Would these intrusions, a trait of Saramago s fictional prose, be a result of the mixed genre? Our corpus is O Ano da Morte de Ricardo Reis. A novel narrated by different voices, all subordinated to the dominant editorial omniscience. This fact aroused questions related to the authorial presence in Saramago s prose. So, it became necessary to undertake an extensive bibliographical study including books, papers and the author works, as well. Investigations were led on literary theory referring to the author, the narrator, the mixed genre and the essay. The study was divided into three parts. The first one was dedicated to reflect on the hermeneutic, the historical studies and the novel criticism. The concepts proposed by Eco, Jameson, and others, were of assistance. The second part was dedicated to the mixed genre, especially between the novel and the essay. Sennet and Adorno s studies provided subsidies. In the third part, themes related to the author and the narrator were addressed. Booth with the implicit-author, and Friedman s typology of point-of-view were of guidance. The relevance of our research lies on the few studies dedicated to the theme. A last investigation aims to understand, whether his literary stile represents a uniqueness. Thus, by means of conclusion, his style is rather a rhetorical one, that lies down its roots at an old tradition of intellectual-writers